Pengaruh Pengetahuan Produk, Persepsi Resiko, Dan Citra Perusahaan Terhadap Keputusan Pembelian (Studi Pada Produk Tabungan Emas Di PT Pegadaian CP Jepara) - Chamidatun Nisa'; Suzy Widyasari (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
This study aims to find out how consumer purchasing decisions are influenced by the risks of product knowledge, perceptions, and corporate image. The sample in this study were loyal customers of Gold Savings at PT Pegadaian CP Jepara. The sample was tested using purposive sampling with a complete sample of 100 respondents who met certain criteria, including around 20 years of age and active customers. The primary data of the researcher is used in this study. This study collected data by distributing questionnaires to Gold Savings customers at PT Pegadaian CP Jepara. Cronbach's alpha reliability test, multiple linear regression test, coefficient of determination test (R2), simultaneous F test, and t test were used in this study.